Syndemic geographic patterns of integrated diseases during the Libyan armed conflict; a new aspect for public health care intervention? - Daw, Mohamed Ali; El-Bouzedi, Abdallah H.; Abumahara, Saleh Ali; Najjar, Abdurrahman Khalifa; Ben Ashur, Nouri R.; Grebi, Alaa; Dhu, Amnnh Mohammed; Alzahra, Emad Elsgair; Alkarghali, Ali Fathi; Mohammed, Shahid Husayn; Miftah, Raja Khalid; Abdulsamad, Najmuldin Abdulbasit; et al. (Frontiers in Epidemiology, 2025)
IntroductionSynedmic geographic analysis is new epidemiological tool used to implement crucial effective intervention to combat integrated diseases. This study aims to determine spatial patterns and geographic profiling of three concurrent diseases including TB/CPVID-19, HIV/HCV, and Mortality/Morbidity in Libya during the Libyan armed conflict.MethodsGeographic thematic mapping and spatiotemporal analysis were used to examine the syndemic geographic profiling of three integrated diseases including COVID-19 and TB, HCV/HIV, and Mortality and Morbidity during the Libyan armed conflict. The total number of notified TB and the cumulative number of COVID-19 cases, HIV and HCV cases, and Mortality and morbidity cases during the conflict period were reported. Such data were obtained at individual and geographic levels from each district involved in the armed conflict then analyzed and classified according to location, timing, and intensity of the Libyan armed conflict.ResultsHigh co-occurrence of TB and COVID-19 was evident. The southern region (i.e., Sebha), Tripoli, and Benghazi consistently portrayed higher incorporation patterns of the two intertwined infections. Conversely, the western mountain region and the Southeast region exhibited a lower concordance during the pandemic period. The co-occurrence of HIV and HCV infections was clear all over the country. The highest condensation of the concomitant is in the Western region, particularly the western mountains, Zawia followed by Jufra and Ghat. Followed by the Eastern region, particularly Deana and Benghazi. This was less tense in the Southern and Med region municipalities. Mortality and morbidity show a visible syndemic geographic pattern. The highest density of these two concomitant patterns was Benghazi, Derna and, Ajdabia in the Eastern region and Sirt, Musrta, Baniwaled in the Western region and to a lesser extent in Zawia and Shati.This study highlights the need syndemic geographic patterns of integrated diseases to focus on wellbeing beyond standard health parameters. Clear decisions about prioritisation of health care to be provided based the geographic region in need.